Analisis Piutang Tak Tertagih Terhadap Sisa Hasil Usaha (SHU) Koperasi Simpan Pinjma Kopdit Pintu Air Cabang Kloangpopot - Yulianti, Maria Helena; Herdi, Henrikus; Jaeng, Wihelmina Maryetha Yulia (Jurnal CUAN Universitas Nusa Nipa Maumere, 2025)
This study aims to determine the impact of uncollectible receivables analysis on the operating results of the Kloangpopot branch of the Pintu Air Savings and Loan Cooperative. Employing a quantitative research methodology with a descriptive approach, this in vestigation examines various financial indicators. The findings reveal that several ratios- including receivable turnover ratio, average collection period (ACP), arrears ratio, collection ratio, effectiveness ratio, and profitability ratios comprising profit margin, ROI (Rate of Total Investment), and ROA (Rate On Total Asset)- Have demonstrated tuitiontion. These fluctuations indicate that the cooperative has not been operating effectively in terms of receivables collection management and has not fully optimized its asset utilization capabilities for long-term sustainability. Despite these fluctuations, the receivable turnover ratio can be considered generally favorable. Furthermore, while exhibiting fluctuation, the profit margin ratio has maintained a percentage above 80% from 2020-2024. These findings suggest that the Kloangpopot branch of the Pintu Air Savings and Loan Cooperative demonstrates sound financial performance and effective cost management strategies conducive to the cooperative’s future growth and development.